Implementation of Biah lughawiyah in Improving Arabic Speaking Skills at the Makkah Madinatul Qur'an Tahfidzul Qur'an Islamic Boarding School - Sunardin Sunardin; Dea Silviani; Biqi Zain (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The purpose of this study is to examine how bi’ah lughawiyyah, or the language environment, functions in improving Arabic speaking skills at Pondok Pesantren Tahfidzul Qur’an Makkah Madinatul Qur’an. This research employed a descriptive qualitative approach, a type of research method aimed at describing and explaining a phenomenon in depth. Data were collected through observation, interviews, and documentation. The results of the study indicate that bi’ah lughawiyyah was implemented through various programs, such as daily conversation habituation, structured muhadatsah (conversation practice), communicative assignments, and the use of Arabic as the medium of instruction in boarding school activities. The language environment was proven to enhance students’ confidence, fluency, and accuracy in speaking Arabic. Discipline, teacher role modeling, and various learning media were identified as supporting factors for the success of the program. Meanwhile, the obstacles encountered included limited initial vocabulary and differences in teachers’ educational backgrounds and abilities. Overall, this study found that bi’ah lughawiyyah is an effective method for improving Arabic speaking proficiency in the Islamic boarding school environment.